On the Development of GFDL's Decadal Prediction System: Initialization Approaches and Retrospective Forecast Assessment. (30th October 2021) - Yang, Xiaosong; Delworth, Thomas L.; Zeng, Fanrong; Zhang, Liping; Cooke, William F.; Harrison, Matthew J.; Rosati, Anthony; Underwood, Seth; Compo, Gilbert P.; McColl, Chesley
Abstract: Using GFDL's new coupled model SPEAR, we have developed a decadal coupled reanalysis/initialization system (DCIS) that does not use subsurface ocean observations. In DCIS, the winds and temperature in the atmosphere, along with sea surface temperature (SST), are restored to observations. Under this approach the ocean component of the coupled model experiences a sequence of surface heat and momentum fluxes that are similar to observations. DCIS offers two initialization approaches, called A1 and A2, which differ only in the atmospheric forcing from observations. In A1, the atmospheric winds/temperature are restored toward the JRA reanalysis; in A2, surface pressure observations are assimilated in the model. Two sets of coupled reanalyses have been completed during 1961–2019 using A1 and A2, and they show very similar multi‐decadal variations of the Atlantic Meridional Overturning Circulation (AMOC). Two sets of retrospective decadal forecasts were then conducted using initial conditions from the A1 and A2 reanalyses. In comparison with previous prediction system CM2.1, SPEAR‐A1/A2 shows comparable skill of predicting the North Atlantic subpolar gyre SST, which is highly correlated with initial values of AMOC at all lead years. SPEAR‐A1 significantly outperforms CM2.1 in predicting multi‐decadal SST trends in the Southern Ocean (SO). Both A1 and A2 have skillful prediction of Sahel precipitation and the associated ITCZ shift. The prediction skill of SST is generally lower in A2 than A1 especially over SO presumably due to the sparse surface pressure observations. Plain Language Summary: In this paper we document the development and skill assessment of a new coupled decadal prediction system. We have developed a decadal coupled reanalysis/initialization system that does not use subsurface ocean observations. Under this approach the ocean component of the coupled model experiences a sequence of surface heat and momentum fluxes that are similar to observations. The new system offers two initialization approaches which differ only in the atmospheric forcing from observations. One approach utilizes the three‐dimensional reanalysis data, while the another only uses the surface pressure observations. We document the process‐based diagnosis of the improved representation of multi‐decadal variations of the Atlantic Meridional Overturning Circulation associated with the observed North Atlantic Oscillation forcing. The skill assessment of the new decadal retrospective forecasts versus observations supports that the proposed approach is feasible for the decadal climate prediction, increasing diversity of modeling tools for the decadal climate initialization and predictability research. The experimental decadal prediction using the new system will be used for the real‐time decadal climate outlooks. Key Points: Development of GFDL's new decadal coupled reanalysis/initialization system is documented The system captures the multi‐decadal variations of Atlantic Meridional Overturning Circulation associated with North Atlantic Oscillation The new system significantly outperforms its predecessor in predicting multi‐decadal SST trends in the Southern Ocean